Pengaruh Social Media Marketing Dan Electronic Word Of Mouth Terhadap Keputusan Pembelian Dengan Brand Image Sebagai Variabel Intervening (Studi Pada Konsumen Produk Kosmetik Wardah Dikalangan Mahasiswa Jurusan Manajemen Angkatan 2022 Upi YPTK Padang ) - Salma Khairiyah Putri (Jurnal Ekonomi dan Bisnis Digital, 2026)
The development of digital technology has transformed consumer behavior in the purchasing decision-making process, particularly through social media. This study aims to analyze the influence of Social Media Marketing and Electronic Word of Mouth on purchasing decisions for Wardah cosmetic products, with Brand Image as an intervening variable among Management students of the 2022 cohort at Universitas Putra Indonesia (UPI) YPTK Padang. This research employed a quantitative approach using accidental sampling, involving 100 respondents from a total population of 900 students. Data were collected through questionnaires and analyzed using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS). The results indicate that Social Media Marketing has a significant effect on purchasing decisions and Brand Image. Electronic Word of Mouth does not have a significant direct effect on purchasing decisions but significantly influences Brand Image. However, Brand Image does not significantly affect purchasing decisions and does not mediate the influence of Social Media Marketing and Electronic Word of Mouth on purchasing decisions. These findings suggest that purchasing decisions are more directly influenced by digital marketing activities rather than through Brand Image.